Comparative description of summer zooplankton of litoral zone and pelagic zone of the north-east bay of lake Markakol (Eurasian Journal of Ecology, 2016)
The composition of species of zooplankton of the north-eastern gulf of Markakol was analyzed during academic research. Biodivercity of zooplankton species in littoral zone is higher than in pelagic zone, but the amount of them is less. First established the rotifers Platyias guadricornis were found in the intertidal zone in the lake of Markakol.
Keywords: zooplankton; litoral; pelagic; diversity; bay; lake.